Gender, social cohesion and everyday struggles in South Africa - Segalo, Puleng (PINS-Psychology in Society, 2024)
Since the advent of democracy in South Africa, far-reaching changes have taken place in many areas of society. While many positive changes have taken place in the new dispensation; however, the promise of democracy has not been fully met. The hope for collectivity and trust in the government system seems to be an ideal to which many are still striving. Using gender as a unit of analysis, this paper interrogates the complexities of democracy and the ideation of social cohesion in a country that contends with perpetual everyday struggles. I will also draw briefly from a research project that I conducted to highlight how women make meaning of their newly found ‘freedom’ and the ways in which they wrestle with perpetual challenges that so many of them continue to face.